Phytochemical profiling and anticancer potential of gardenia latifolia extracts against arsenic trioxide induced liver fibrosis in rat model - Mehboob, Zahid; Sharif, Sumaira; Lodhi, Madeeha Shahzad; Shah, Abdul Bari; Romman, Muhammad; Nayila, Iffat (Frontiers in Pharmacology, 2024)
Introduction Arsenic trioxide (As2O3) is an environmental contaminant that may cause hepatic injuries. As2O3-induced liver injuries are detected as an underlying cause of hepatocellular carcinoma (HCC) around the globe. The present study aimed to investigate the potential of Gardenia latifolia (GL) extracts against oxidative stress and apoptotic activity in HCC-induced rats and to explore in silico molecular docking analysis of phytocompounds of G. latifolia. Methods The present study was designed to investigate the hepato-protective effect of ethanol and n-hexane extract of G. latifolia. Phytochemical analysis was performed using gas-chromatography-mass spectrometry (GC-MS), and the identified metabolites were used for computational docking analysis. The binding potential and inhibitory effect of the identified metabolites against inflammatory markers were assessed. Fifty male albino rats were selected for the in vivo study and were randomly divided into five groups, with 10 rats in each group. Group I is the control group. Hepatotoxicity was induced in groups II, III, IV, and V with 350 mg/kg/day of As2O3. Group II was taken as positive control, Group III and IV were treated with ethanol and n-hexane extract of G. latifolia, respectively, and Group V was treated with cisplatin 3.0 mg/kg/day. At the end of treatment, different stress and liver biomarkers were also analyzed. Results and Discussion The quantitative phytochemical profiling revealed a high content of total flavonoid and tannins found at 5.731 ± 0.1856 mg quercetin equivalent (QE)/g and 86.31 ± 14.20 mg tannic acid equivalent (TAE)/g in G. latifolia n-hexane extract, while a significant concentration of TFC was 276.821 ± 2.19 mg gallic acid equivalent (GAE)/g, in ethanolic extract. GC-MS analysis resulted in the identification of 26 metabolites in ethanol extract while 32 metabolites in n-hexane extract, respectively. Both the extracts restored the abnormal levels of stress markers (p < 0.05) in Groups III and IV, and were comparable to the comparative control group V, which was given cisplatin as the standard drug. The histopathological examination revealed the regeneration of hepatocytes, dilated sinusoidal cells, necrosis, and distorted hepatic architecture observed in arsenic trioxide hepatotoxic liver. Among the top most identified metabolites from GC-MS analysis, stigmasterol exhibited −8.3 and −7.1 kcal/mol in silico binding affinities against cyclooxygenase-2 (COX-2), and interleukin (IL-6), respectively, while Dasycarpidan-1-methanol exhibited the best binding affinities of −6.8 and −7.2 kcal/mole against matrixmetalloprotinease (MMP)-3 and heat shock protein-90 (HSP-90), respectively. 6-AH-cAMP showed the best docking score of −7.5 kcal/mol for the vascular endothelial growth factor (VEGF) macromolecule. Metabolite Dasycarpidan-1-methanol, acetate represented drug like properties so it was further analyzed by MD simulation and stable dynamic nature of protein ligand complex was evaluated. Conclusion In conclusion, the effective therapeutic potential of G. latifolia extracts targeted oxidative stress, increasing antioxidant activities and inhibiting inflammation and liver complications at early stages. Further research on the molecular level may further explore the anticancer potential of this plant against various types of cancers.